POSITIVE FACTORS AFFECTING THE MORALE OF MODERN LEADERS: PROBLEMS AND SOLUTIONS - Masharipov Ikramjon Batirovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
In this article, in order to create a compact state management system that meets modern requirements in the conditions of New Uzbekistan, to increase the responsibility of the heads of state bodies by simplifying the processes of decision-making and consideration of the issue, and to direct their activities to efficiency, as well as to restore and develop the traditions of national statehood in the fields of state and community building. The author's opinions were formed based on the importance of paying attention to the formation of the professional culture of the leaders on the basis of spiritual factors, and the research of the positive factors affecting the spiritual growth of the leaders, who are the most important layer of the state and society management, and the moral and ethical criteria related to the management activities.